PENGARUH KEKUASAAN DAN KEPERCAYAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA GURU SEKOLAH DASAR NEGERI (SDN) DI RAWALUMBU BEKASI - Jamilah Syairoh (Universitas Negeri Jakarta, 2013)
The objective of this research is to obtain information about the effect of power and trust on teachers organizational citizenship behavior (OCB). This research used survey method with path analysis. Sample in this research was used simple random sampling.The conclusions of this research are: (1) There is a positive direct effect of power on organizational citizenship behavior (OCB). (2) There is a direct positive effect of trust on teacher organizational citizenship behavior (OCB). (3) There is a positive direct effect of power on trust.